2013
DOI: 10.1038/gim.2012.113
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences receiving abnormal prenatal chromosomal microarray testing results

Abstract: Purpose Genomic microarrays can detect copy number variants not detectable by conventional cytogenetics. This technology is diffusing rapidly into prenatal settings even though the clinical implications of many copy number variants are currently unknown. We conducted a qualitative pilot study to explore the experiences of women receiving abnormal results from prenatal microarray testing performed in a research setting. Methods Participants were a subset of women participating in a multicenter prospective stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
244
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(254 citation statements)
references
References 38 publications
9
244
1
Order By: Relevance
“…A psychosocial analysis of 23 women who received prenatal CNV analysis as part of their prenatal care revealed that many women were unprepared for uncertain results and that this increased the psychological burden associated with the pregnancy [69]. Improvements in understanding the postnatal implications of CNVs will provide additional resources in the prenatal setting.…”
Section: Cnvs In Fetal Chdsmentioning
confidence: 99%
“…A psychosocial analysis of 23 women who received prenatal CNV analysis as part of their prenatal care revealed that many women were unprepared for uncertain results and that this increased the psychological burden associated with the pregnancy [69]. Improvements in understanding the postnatal implications of CNVs will provide additional resources in the prenatal setting.…”
Section: Cnvs In Fetal Chdsmentioning
confidence: 99%
“…Before this can be ascertained, VOUS must be awarded an effectiveness score. Current qualitative data seems to suggest that parents have mixed feelings about their worth, depending upon whether they are given pre- or postnatally and that prenatally they may be given a limited value, or even a negative value [23]. If awarded a negative value it may be better to not report them to parents at all.…”
Section: Discussionmentioning
confidence: 99%
“…95, 96, 97 These findings complicate pre-test counseling and when detected, cause significant distress and difficulty with decision-making. 2 …”
Section: Chromosomal Microarray Analysismentioning
confidence: 99%
“…Thus, couples frequently find themselves needing to make decisions in the face of considerable uncertainty. 2 …”
Section: Chromosomal Microarray Analysismentioning
confidence: 99%
See 1 more Smart Citation